'Many Europes' vs. secessionism: the case of Catalonia. Issue 5 (20th October 2021) - Gulmez, Seckin Baris; Buhari-Gulmez, Didem
ABSTRACT : Following the four-fold taxonomy advanced in this special issue, this study explores the divergent motivations behind the varying European attitudes towards Catalan independence and the resulting ambivalence in the official EU discourses. It will first lay out the main political context underlying the question of Catalan secession from Spain. It will then discuss the main attitudes of the EU officials towards the Catalan independence which reflect a dualistic approach to secessionism in general. The final part will apply the analytical categories this special issue puts forward as 'Thin, Thick, Parochial and Global' Europes revealing the co-existence of multiple ways of imagining Europe and its borders. According to the study, the EU's inertia and ambiguous rhetoric towards the Catalan secessionism show that the EU is caught up between Thin and Thick European visions which respectively underscore the EU's neutrality towards an 'internal matter' of Spain and an anti-secessionist attitude prioritizing European stability, solidarity and integrity. In spite of their divergent perspectives, their stances towards Catalan independence converge in terms of advocating regionalism and internal self-determination. Parochial and Global Europes are discussed as alternative unofficial trends affecting the future of European borders.